Effect of particle size distribution on Acoustic Doppler Velocimeter backscatter for suspended sediment measurements. (June 2021) - Sahin, Cihan
Abstract: The capability of acoustic Doppler velocimeters (ADVs) to estimate suspended sediment concentration has been widely investigated using glass microspheres of the same size or well-sorted fractions in experimental studies. Sediment mixtures in the natural environment may have various types of grain size distribution. This study aims to investigate experimentally the acoustic response to probability distributions in suspension including quite coarse sediment fractions up to a diameter of 300 μ m. Modification of scattering and attenuation characteristics by introducing a size distribution is evaluated using the formulations given in the literature. In laboratory experiments, three different types of sediment size distributions constituting a wide size range of non-cohesive quartz sediments, namely uni-modal mass distribution, bi-modal mass distribution, and uniform number distribution, were generated. Acoustic backscatter measurements were made by immersing the ADV in a circulation tank filled with mixtures of sediments with known concentration and particle size distribution. Acoustic estimates of suspended sediment parameters obtained for different particle size distributions are compared with those for mono-size particle suspensions to show the effect of introducing a size distribution in suspension. The acoustic response from size distributions agrees with the general theoretical behavior such that the slope of the calibration curve decreases as the sediment size increases. The scattering and attenuation properties are modified compared to the mono-size suspension with the same mean size. In a region close to the geometric scattering regime, the backscattering coefficients for the particle size distributions are around 34% lower than those for mono-size particles, which results in lower backscattering strengths compared to the mono-size suspensions under the same concentration conditions. The sediment attenuation coefficient showed a smaller reduction (11%), resulting in a negligible change in the calculated signal corrected for water and sediment attenuation compared to the values for mono-size suspension of the same particle size. The information on the form of the probability distribution and the sorting of sediments in suspension is important for acoustic estimates of suspended sediment parameters. Introducing a particle size distribution affects the scattering properties more significantly than the attenuation properties for the geometric scattering regime. Highlights: Acoustic response to PSDs is investigated experimentally and theoretically. Scattering and attenuation properties are modified compared to mono-size suspension. Introducing a PSD affects scattering properties more significantly than attenuation.